Perovskite nanoparticles synthesised by reactive milling combined with thermal processing: preparation, morphology and structure characterisation. (24th January 2011) - Manh, Do Hung; Thanh, Tran Dang; Phuc, Nguyen Xuan; Hong, Le Van; Phong, Pham; Hung, Luu
Reactive milling and thermal processing methods were used to prepare a large variety of perovskites like ABO3 and La2 NiO4 . The single-phase nanoparticle of ABO3 was synthesised at different milling times in dependence on the starting oxides. The grain size of ABO3 nanoparticles in the range of 10-30 nm was conditional upon milling time. Single-phase nanoparticles of La2 NiO4 were obtained by using 6 h milling combined with annealing at 750°C. A structure conversion from a layer into a single perovskite of La2 NiO4 was observed as milling time increased, whereas the crystalline structure of ABO3 remained almost unchanged. Further analysis of HRTEM images confirms a core-shell structure of nanoparticles.